An INFORMAL URBANISM IN CITIES: LITERATURE REFLECTION IN 30 YEARS - firmansyah, ade (Tata Kota dan Daerah, 2023)
Cities and urban areas are faced with heterogeneous conditions, physically, socially, environmentally and economically. Many academics believe that urban heterogeneity creates a two-sided urban face. Conditions that tend to show these comparisons lead to the formal and informal conceptions of urban areas. Informal urbanism has increased in recent years to become a growing political object and a scientific concern for some researchers or academics. This article attempts to identify research flows and research priorities in the field of informal urbanism based on an analysis of the literature from 1997 to 2022, including 1,056 documents from the Scopus database. The author uses two software, namely Bibliometrics (Biblioshiny) and VOSviewer, for performance and network mapping analysis. The results show that the field of informal urbanism has grown from the aspect of the number of publications in the past 30 years. Analysis based on country shows that the majority of developed countries outperform other countries in producing publications on informal urbanism. The results of this study can help academics and researchers by providing important insights into the field of urban research.